Literary Learning on Main Character’s Motivation in Up Film: A Psychological Approach - Fransiskus Maria Separ; Maxima Owa (Universitas Muhammadiyah Enrekang, 2023)
The aim of this study is to find the kinds of motivation and the way to survive in Up film. In this study, descriptive qualitative method was addopted to describe the utterances and actions of the character. Psychological approaches was applied to analyze the kinds of motivation and the way to survive. The theories used to analyze the kinds of motivation was proposed by Runyon (1984), while to analyze the way to survival, the theory proposed by McClleand (1987) was used. The results of the study shows that there are four kinds of motivation namely intrinsic motivation, extrinsic motivation, contributive motivation, and relational motivation. Meanwhile the ways to survive in Up film are needs of achievement, needs of affiliation, and needs of power.